Effectiveness of Infant Massage and Classical Music Therapy on Sleep Quality Among Children Aged 6-12 Months - Zayani, Zayani; Pabidang, Siswanto; Maimunah, Siti (Open Access Health Scientific Journal, 2025)
Background: Infant sleep quality is crucial for growth and development, yet many infants experience sleep disturbances. This study explores the effectiveness of non-pharmacological interventions, massage and classical music in improving sleep quality in infants.Methods: This study was conducted at Puskesmas Gogagoman in North Sulawesi, involving 48 infants aged 6–12 months, randomly assigned to massage, classical music, or control groups. Using a quasi-experimental pretest-posttest control group design, researchers assessed sleep quality before and after interventions. Data were collected using the Brief Pittsburgh Sleep Quality Index (B-PSQI) and analyzed using non-parametric tests, including the Wilcoxon Signed Ranks Test and Kruskal-Wallis Test.Results: The major findings of this study indicate that infant massage significantly improved sleep quality compared to both classical music therapy and the control group. After the intervention, the massage group showed the greatest reduction in sleep disturbance scores (mean score dropped from 2.88 to 1.13), followed by the music group (mean score dropped to 1.94), while the control group showed minimal change (mean score of 2.81). Statistical tests confirmed that these differences were significant, highlighting that massage therapy was the most effective intervention for enhancing infant sleep quality.Conclusion: This study concludes that infant massage is more effective than classical music in improving sleep quality in infants. Both interventions were better than no treatment.